The Effect of Liquidity, Solvency, Profitability and Activity Ratios on Company Value in Food & Beverage Sub-Sector Manufacturing Companies Listed on the IDX in 2019-2023 - Muhammad Fadhilsyah; Andini Utari Putri; Mutiara Kemala Ratu (Transpublika Publisher, 2025)
The food and beverage industry in Indonesia, particularly companies on the Indonesia Stock Exchange (IDX), is dealing with economic challenges affecting financial performance and market value. Challenges include decreased consumer purchasing power, higher production costs, and market uncertainty leading to low investor confidence. This situation complicates the evaluation of company value, requiring a thorough understanding of factors influencing value, such as financial ratios. This study has originality in examining the effect of financial ratios such as liquidity, solvency, profitability, and activity on company valuation in the food and beverage sector listed on the IDX. This study aims to explore the relationship between these ratios and firm value in the period 2019 to 2023, and provide a clearer picture for investors and managers in making strategic decisions based on solid financial data. The research in this study is conducted using a quantitative approach. A deliberate sampling technique was used to choose 27 businesses within a 5-year timeframe, totaling 135 samples. Secondary data from www.idx.co.id was utilized for the analysis through the use of multiple linear regression in the SPSS version 26 software. The findings of the research reveal that company value is influenced significantly by liquidity (CR), solvency (DER), profitability (ROA), and activity (TATO). The results show simultaneously that the influence of liquidity, solvency, profitability and activity has an effect on company value. This research aims to provide investors with precise financial insights while establishing frameworks for future studies that incorporate additional factors and broader sampling periods.